Case 3845: Proposed confirmation of the type species of Pseudochloritis Boettger, 1909, with the preservation of Helix incrassata Klein, 1853, a junior primary homonym of Helix incrassata Reeve, 1853 (Mollusca, Gastropoda, Helicoidea) - Kadolsky, Dietrich (Bulletin of Zoological Nomenclature)
Noticed in BZN 78 (30 Apr 2021): 2.